Free-standing polypyrrole/polyaniline composite film fabricated by interfacial polymerization at the vapor/liquid interface for enhanced hexavalent chromium adsorption. Issue 10 (13th February 2019) - Thao, Vu Dinh; Giang, Bach Long; Thu, Tran Viet
Abstract : Free-standing polypyrrole/polyaniline composite film fabricated by interfacial polymerization at vapor/liquid interface. Abstract : Interfacial polymerization is an innovative technique for the fabrication of polymeric films. However, the majority of studies on interfacial polymerization has focused on liquid/liquid interfaces, and little work has been done on vapor/liquid interfaces. In this paper, we present the fabrication of free-standing polypyrrole/polyaniline (PPy/PANI) composite films by interfacial polymerization at a vapor/liquid interface using FeCl3 as an oxidant. The obtained PPy/PANI composite films were characterized using Fourier transform infrared spectroscopy, X-ray diffractometry, and scanning electron microscopy. It was found that the PPy/PANI composite films consist of PANI particles evenly distributed on porous PPy film. The influence of FeCl3 concentration on the morphology of the resulting composite films was investigated. The PPy/PANI composite films show an excellent Cr(vi ) adsorption capacity of 256.41 mg g −1, much higher than that of PPy-based absorbents prepared from chemical and electrochemical polymerization routes. This work thus suggests a new route for the fabrication of PPy/PANI films with highly enhanced Cr(vi ) adsorption capacity for practical applications.